The Impact of Enterprise Risk Management (ERM) on Corporate Performance: The Case of Non-financial Listed US Companies - Jiang, Yue (2019)
The outbreak of the 2008 financial crisis and the failure of traditional silo-based risk management have prompted people to turn their attention towards a more advanced risk management paradigm, enterprise risk management (ERM). However, even though now there is a continuous development of ERM, it is still practiced at a low level in the non-financial industry. Under such a circumstance, this study aimed to conduct empirical research in order to find answers to the following questions: How is ERM developing in non-financial companies? Is ERM also valuable to them? Based on previous studies and the actual situation of the US market, this study constructed an index system in order to measure the sophistication of the ERM practice of the selected companies. By examining the data of 68 non-financial listed companies in the US between 2005 and 2018, this study constructed several panel data models in order to empirically analyse the relationship between the ERM practice of the companies and their accounting and market performance. The empirical results showed that the companies that practice ERM on an advanced level have better market and accounting performance than those who do not. Furthermore, it was also found that the establishment of risk committees can significantly improve a company’s performance from both the performance measurement perspectives. However, the chief risk officer (CRO), who is often seen as a sign of ERM implementation, was found to have no significant contribution to a company's performance improvement. This study introduces some references for enterprises to help them design risk management system rationally, improve risk management ability and enhance enterprise value. Moreover, it provides new evidence for comprehensive understanding and evaluation of the value of ERM.